Motivational career counselling and coaching cognitive and behavioural approaches - Sheward, Steve; Branch, Rhena (SAGE Publications, 2012)
This thoroughly practical book combines cognitive and behavioural approaches with vocational counselling and coaching providing clear, practical strategies and a wealth of materials that can be used with clients in one-to-one or group settings